Integrated farming system approaches for enhancing crop productivity, profitability, employment and soil sustainability - DESAI, L.J.; PATEL, K.M.; PATEL, P.K.; PATEL, VIDHI K. (Journal of Soil and Water Conservation, 2025)
Integrated farming systems assumes greater importance for sound management of farm resources to enhance the farm productivity and reduce the environmental degradation, improve the quality of life of resource-poor farmers and maintain sustainability. An experiment of integrated farming system (IFS) model comprising of 1.0 ha area was conducted during 2010–11 to 2018–19 at the Centre for Research on Integrated Farming Systems, Sardarkrushinagar, Dantiwada Agricultural University, Sardarkrushinagar of Gujarat for validation of an IFS model. There were four cropping system and allotted area was 0.70 ha, viz. castor (Ricinus communis L.) + greengram (Vigna radiate (L.) R. Wilczek] (0.32 ha); groundnut (Arachis hypogaea L.)– wheat (Triticum aestivum L.)-multicut fodder pearl millet [Pennisetum glaucum (L.) R. Br.] (0.08 ha); greengram Indian mustard [Brassica juncea (L.)Czernj.]–pearlmillet (0.24 ha); and hybrid napier [Pennisetum purpureum (Schumach)] + fodder cowpea [Vigna unguiculata (L.) Walp.]–Lucerne (Medicago sativa L.) + fodder chicory (Cichorium intybus L.) (0.06 ha) based on small and marginal farm family requirement. N addition to that fruits and vegetable in two tiers were sown on 0.25 ha. Making microbes-enriched vermin-compost from the waste and dung of the two buffaloes (Bubalus bubalis) reared on 0.025 ha. Farm wastes were recycled within the system which obliterated the need to purchase offfarm inputs. The internal bunds of cropping systems was used for growing fodder, while farm boundary with quick-growing timber tree. The model had a provision of farm pond (0.015 ha) for water harvesting and well recharging on low-lying depression of the farm. Groundnut - wheat -multicut fodder rajka bajra + horticultural and vegetables crops +livestock+ vermi compost + boundary plantation + farm pond registered significantly higher groundnut equivalent yield (GEY) (8696 kg/ha), which was statistically at par with IFS Model (castor + greengram (032 ha) + groundnut - wheat -multicut fodder rajka bajra (0.08 ha)+ greengram -Mustard-Pearl millet (0.24 ha)+ Hy. napier +cowpea (F) - lucerne + fodder chicory (0.06 ha)+Horticultural and vegetables crops (0.25 ha) +Livestock(0.025 ha) + vermi compost (0.010 ha)+ boundary plantation + farm pond (0.015 ha) (7977 kg/ha)and same treatment registered significantly higher employment generation (476 mandays/year).